PERANAN PSIKOLOGI DALAM MANAJEMAN SUMBER DAYA MANUSIA PADA PERUSAHAAN JASA - Amara Mutiara Santoso; Annisa Khurrotul Luthfil Aini; Jesyinda Putri Wibowo; Niken Bela Enggarani; Oktiane Bulan Indah; Arfian (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This study discusses the role of psychology in Human Resource Management (HRM) within service companies using a literature review approach. The findings reveal that psychology contributes to various HRM functions, including recruitment and selection, employee training and development, work motivation, and the establishment of a supportive work environment. The application of psychological principles enables organizations to better understand employees’ characteristics and potential, which can improve job satisfaction, productivity, and service quality. Therefore, psychology serves as a key element in effective human resource management and supports the achievement of organizational goals.